Insights into activated sludge/Chlorella consortia under dark condition compared with light condition. (10th October 2022) - Fan, Jie; Zhang, Xujie; Du, Xingyu; Cai, Zhenlei
Abstract: Bacteria–algae consortia in the light bring the benefit of O2 production and CO2 reduction for wastewater treatment, while the bottleneck for application is how it behaves in the dark. In this study, inoculum ratio and sludge retention time (SRT) affected nutrient removal rather than chemical oxygen demand (COD) removal. Dark conditions (with a sludge/ Chlorella inoculum ratio of 1:2 at a SRT of 15 d) achieved comparable performance to those of light conditions, due to bacteria contribution and mechanical aeration. Compared with light conditions, the ratio of Chl a /Chl b decreased and Caro/(Chl a + Chl b ) increased to response oxidative stress. In the dark, algae were associated with Nitrosomonas and Dechloromonas . Flavobacterium disassociated with Chlorella in the dark but associated with Chlorella in the light . Moreover, nitritation genes ( amo and Hao ) and denitrifying gene ( narH ) were up-regulated, while P metabolism genes ( PPX and PPK ) were down-regulated. It is proposed to enrich Nitrosomonas in the night and denitrify polyphosphate accumulating organisms (DPAO) in the daytime to establish short-cut nitrification and denitrifying phosphorus removal in practical applications. HIGHLIGHTS: Bacteria–algae inoculum ratio affected N and P removal, while SRT affected P removal. Bacteria contributed more than algae towards COD, NH4 +, and P removal. Caro/(Chl a + Chl b ) increased and Chl a /Chl b decreased. Dark co-culture favored Nitrosomonas but was adverse to Flavobacterium . N-related genes ( amo, Hao, narH ) were up-regulated, while P-related genes ( PPX, PPK ) were down-regulated. Graphical Abstract